Karstmorphologische Untersuchungen auf Kreta - Bartels, Gerhard (ERDKUNDE, 1991)
In 1988/90 fieldwork was carried out on poljes in the Karst of the island of Crete. From these field observations we can draw the following conclusions: The formation of poljes was facilitated by downfaulting. Poljes developed without tectonic influence remained relatively small. Nearby outcropping impermeable rock supported the formation of poljes. Noncarbonate detritus was transported into the depressions and luted the joints beneath their floors. Otherwise poljes developed far away from outcropping impermeable rock. Therefore the insoluble residue must have affected the jointed limestone similarly. Slopes surrounding the poljes and slopes of the humi were steepened by lateral corrosion under recent climatic conditions even at heights of 1400 m, but the floors of some high-lying depressions are being destroyed by downwearing. The formation of poljes started probably in the Early Quaternary or even in the Late Pliocene.